Correction: The genetic identity of neighboring plants in intraspecific mixtures modulates disease susceptibility of both wheat and rice. - Rémi Pélissier; Elsa Ballini; Coline Temple; Aurélie Ducasse; Michel Colombo; Julien Frouin; Xiaoping Qin; Huichuan Huang; Jacques David; Florian Fort; Hélène Fréville; Cyrille Violle; et al. (PLoS Biology, 2023)
[This corrects the article DOI: 10.1371/journal.pbio.3002287.].